Kajian Konsep Teknologi Pengolahan Pasir Zirkon Lokal yang Mengandung Monasit, Senotim dan Ilmenit - Poernomo, Herry; Biyantoro, Dwi; Purwani, Maria Veronica (BRIN Publishing, 2016)
The existence of zircon (ZrSiO4) in the nature is mostly associated with some of the valuable oxide compounds (VOC), such as TiO2 and rare earth oxides (REO). The existence of natural minerals in Indonesia containing zirconium (Zr) and REO lies in 13 regions, ranging from Aceh to West Papua province. Based on those aforementioned aspects, the goal of this research is to conduct the study of integrated technology of local zircon sand processing containing TiO2 and REO. The study was conducted by analyzing the content of VOC in zircon sand samples from the areas of Landak and Tumbang Titi West Kalimantan and Bangka by using XRF. Based on the content of VOC in this zircon sand, it can be predicted that the zircon sand from the area of Landak and Tumbang Titi West Kalimantan and Bangka contains mineral zircon (ZrSiO4), ilmenite (FeTiO3), monazite (LREE, Th)PO4, and xenotime (HREE, Th)PO4. Based on these types of mineral, the flow chart of beneficiation technology process to increase the concentration of each mineral and the flow chart of zircon concentrate process into ZrO2(zirconia) and ZrOCl2.8H2O (zirconium oxychloride) industrial grade and zirconia and zirconium chemicals nuclear grade, ilmenite into TiO2, monazite into Nd2O3, and Th(OH)4 concentrate, xenotime into Y2O3, Gd2O3, and Th(OH)4 concentrate are obtained in one area of pilot plant or an integrated factory. The results of the study concluded that the concept of local processing of zircon sands containing monazite, xenotime, and ilmenite can be either integrated in the region with the results of multi-product plant. If it can be realized in Indonesia with the addition of an integrated waste water treatment system, then in addition to safe for the environment can also save on production costs and give economic added value for shareholders zircon mining permit.